Uji Efek Antipiretik Infusa Batang Brotowali (Tinospora Crispa (L.) Miers) Pada Tikus Putih Jantan Galur Wistar Yang Diinduksi Vaksin Dpt - Wulandari, Yayuk; , dr. Rochmadina Suci Bestari M.Sc (2016)
Background: The use of herbal medicine has been known for centuries and it is principled on the use of natural material. Herbal medicines have fewer side effects than conventional medicine. Brotowali (Tinospora crispa (L.) Miers) is one of 300 species of herbal medicine which commonly used for many medications. One of the effect of Brotowali as herbal medicine is antipyretic or fever medication. Fever is a common disease and most people consider fever is a mild illness that can heal it self. In fact, there are some types offevers that should be treated because of several indications. Antipyretic drug is rarely used to cure the fever because of its long-term side effect that emerges from the use of chemicals. Brotowali as herbs that have Alkaloid Barberine is one of the herbal medicines for reduce fever. Objective: To proof that the infusion of Brotowali stems (Tinospora crispa (L.) Miers) have potential to be antipyretic on DPT vaccine induced male Wistar rats. Methods: This research is laboratory experimental research with true experiment pre and posttest with control group design. The analyzed variable is DPT vaccine induced male Wistar rats' rectal temperature. Rats that contracted fever given the infusion of brotowali stems with the dosage concentration of 20%, 40% and 80% to see the effect of declining rectal temperature every 15 minutes up to 120 minutes. Data gained from the experiment is analyzed using paired t-test to see the fever effect from DPT vaccine and one way anova test to see the effect of brotowali stems infusion on antipyretic effect percentage t(90) & t(120). Results: The paired t-test showed the result of p<0,05, it means that DPT vaccine induction can cause the fever. One way anova test t(90) & t(120) showed the result of p<0,05 which means the infusion of brotowali stems give significant effect on fever declining in the minute of 90 or 120. Conclusion: The infusion of brotowali stems (Tinospora crispa (L.) Miers) has the most excellent antipyretic effect using the dosage number 2 (40%) in the minutes of 90 and 120.